2008
DOI: 10.1111/j.1600-6143.2007.02056.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver Retransplantation in Children: A SPLIT Database Analysis of Outcome and Predictive Factors for Survival

Abstract: To examine outcomes and identify prognostic factors affecting survival after pediatric liver transplantation, data from 246 children who underwent a second liver transplantation (rLT) between 1996 and 2004 were analyzed from the SPLIT registry, a multi-center database currently comprised of 45 North American pediatric liver transplant programs. The main causes for loss of primary graft necessitating rLT were primary nonfunction, vascular complications, chronic rejection and biliary complications. Three-month, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
95
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(110 citation statements)
references
References 29 publications
14
95
1
Order By: Relevance
“…In our study, since 1992, in 4.4% of LTs an eRe‐LT was necessary. In 67% of the patients, vascular complications led to the need for eRe‐LT, whereas in the remaining 33% the cause was PNF, similar to reports in other pediatric series …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our study, since 1992, in 4.4% of LTs an eRe‐LT was necessary. In 67% of the patients, vascular complications led to the need for eRe‐LT, whereas in the remaining 33% the cause was PNF, similar to reports in other pediatric series …”
Section: Discussionsupporting
confidence: 85%
“…In a large single‐center series of children undergoing LT, Venick et al found that eRe‐LT was an independent prognostic factor for poor outcome . Ng et al reported the results of re‐LT in children registered in the Studies of Pediatric Liver Transplantation database from the United States . The authors showed that children who underwent re‐LT ≤30 days after the first LT (eRe‐LT) had a significantly lower survival rate (1‐ and 4‐year patient survival rates of 59% and 56%, respectively) compared with children who underwent late re‐LT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 An extensive series of publications from the SPLIT research group have already examined important factors influencing outcome related to diagnosis, including biliary atresia 5 and fulminant liver failure, 6 for complications such as rejection, 7 infection, 8 diabetes, 9 renal dysfunction, 10 and other known factors important to outcome such as retransplantation, 11 age at transplant, 12 graft type, 13 and surgical complications. 14 In this study, our hypothesis is that multivariate analyses of the comprehensive range of factors from the pre-, peri-, and posttransplant periods recorded in the SPLIT database will elucidate the most important variables affecting patient and graft survival 6 months after transplantation.…”
mentioning
confidence: 99%
“…16 Age at diagnosis, severity of illness, and possibly the technical variants of grafts utilised (reduced-size and split grafts), may be associated with increased morbidity and decreased overall survival. 17 Ng et al reported second and third transplantation rates of 12% and 2%, respectively, 5% chronic rejection, and 6% post-transplant lymphoproliferative disease in their paediatric LT cohort. 18 Although tests of graft function were preserved in 90% of 5-year survivors in the cohort, one-third of children did not have complete normalisation of liver enzymes, suggesting ongoing graft inflammation.…”
Section: Outcome and Graft Survival Following Ltmentioning
confidence: 99%